2007
DOI: 10.1002/jssc.200700346
|View full text |Cite
|
Sign up to set email alerts
|

Alkylated poly(styrene‐divinylbenzene) monolithic columns for μ‐HPLC and CEC separation of phenolic acids

Abstract: Macroporous poly(styrene-divinylbenzene) monolithic columns were prepared in fused silica capillaries of 100 microm id by in-situ copolymerization of styrene with divinylbenzene in the presence of propan-1-ol and formamide as the porogen system. The monoliths were subsequently alkylated with linear alkyl C-18 groups via Friedel-Crafts reaction to improve the retention and chromatographic resolution of strongly polar phenolic acids. A new thermally initiated grafting procedure was developed in order to shorten … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…In our previous study, we demonstrated the synthesis and surface modification of monolithic PS-DVB columns that were used for liquid chromatographic and electrochromatographic separations of organic acids [17]. In general, the PS columns can be alkylated using FC reaction, as well as grafted with octadecyl methacrylate to change their selectivity during the chromatographic/electrochromatographic separation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, we demonstrated the synthesis and surface modification of monolithic PS-DVB columns that were used for liquid chromatographic and electrochromatographic separations of organic acids [17]. In general, the PS columns can be alkylated using FC reaction, as well as grafted with octadecyl methacrylate to change their selectivity during the chromatographic/electrochromatographic separation.…”
Section: Resultsmentioning
confidence: 99%
“…Monolithic capillary columns were prepared according to the procedure published elsewhere in detail [17]. Three types of columns (all of them were of the same dimensions; L tot 5 33.5 cm, L eff 5 25 cm) were synthesized.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, polystyrene monoliths are broadly successfully applied for highly efficient separations of biomolecules in HPLC. These monoliths are chemically stable under a wide pH range and the morphology can be adjusted by the copolymerization of other monomers and the selection of the proper porogenic solvent [27][28][29]. Despite their widespread use in HPLC, the research on the use of polystyrene monoliths (and stationary phase in general) in CEC is still fairly limited.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Materials suitable for the fabrication of the monolithic bed are divided into two main categories: silica [6][7][8] and polymer [9][10][11][12][13][14][15][16] monolith. Silica monolithic columns have well-controlled pore structure, good mechanical strength, and high column efficiency, 7,8 while polymer monolithic columns have unique features such as applicability over a wide pH range and simplicity of preparation.…”
Section: Introductionmentioning
confidence: 99%